Resistance to Gender Equality: Criticism of Physical Violence from the PKDRT Law Perspective - Moh Rosil Fathony; Latifatul Khiyaroh; Suud Sarim Karimullah; Muhammad Taufik Kustiawan (Indonesian Journal of Islamic Law, 2024)
Domestic violence (DV) often occurs, especially in the form of physical violence against women (wives). To protect victims of domestic violence, the state has enacted the Law on Protection of Victims of Domestic Violence (UU PKDRT). Therefore, this study focuses on the phenomenon of victims' views on physical violence in the household in the community of Tegalrejo Village, Mayang District, Jember Regency from the perspective of the PKDRT Law. This study aims to understand and analyze the views of victims on physical violence in the household in depth in the community of Tegalrejo Village, Mayang District, Jember Regency. In addition, this study also aims to evaluate the implementation of Law No. 23 of 2004 concerning PKDRT in the community of Tegalrejo Village. This research was conducted in the field (field research) with a juridical-normative approach with a qualitative descriptive nature through data collection from interviews and documentation. The results of this study state that the views of victims in Tegalrejo Village, Jember Regency towards physical violence in the household still tend to be conservative because various problems are still found in the implementation of the PKDRT Law so the knowledge of the Tegalrejo Village community regarding the law is still limited. The factors that cause this are the lack of government socialization regarding the PKDRT Law to the community, especially in villages, and the lack of public awareness of the problem of domestic violence which is often considered commonplace.